2017
DOI: 10.1097/id.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Implant-Supported Overdenture and Conventional Complete Denture in Restoring the Edentulous Mandible

Abstract: Regarding the edentulous mandible, patients benefited more from the IOD with 2 implants, as determined by OHRQoL scores. Considering the differences between each domain of the Oral Health Impact Profile (OHIP) questionnaire and the lack of long-term performance, more random control trials with sufficient sample sizes need to be designed to investigate long-term performance after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
2
31
0
6
Order By: Relevance
“…on the OHRQoL, similar to other studies albeit with more patients and a longer follow-up (Bilhan, Geckili, Sulun, et al, 2011;De Bruyn et al, 2015;Fernandez-Estevan et al, 2015;Khalid et al, 2017;Kleis et al, 2010;Reissmann et al, 2017;Zhang et al, 2017). The improved OHRQoL is present in all seven sub-domains of the OHIP-14 total score, contrary to other authors (Khalid et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…on the OHRQoL, similar to other studies albeit with more patients and a longer follow-up (Bilhan, Geckili, Sulun, et al, 2011;De Bruyn et al, 2015;Fernandez-Estevan et al, 2015;Khalid et al, 2017;Kleis et al, 2010;Reissmann et al, 2017;Zhang et al, 2017). The improved OHRQoL is present in all seven sub-domains of the OHIP-14 total score, contrary to other authors (Khalid et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…A 2IOD is a satisfying, functional solution for the edentulous patient with a high implant survival rate (De Bruyn, Raes, Matthys, & Cosyn, ; Kern, Kern, Wolfart, & Heussen, ). Recent reviews, evaluating bar and ball connections, predominantly in short‐term studies, showed that an IOD in general has a positive effect on the oral health‐related quality of life (OHRQoL) of the edentulous patient (De Bruyn et al, ; Reissmann, Dard, Lamprecht, Struppek, & Heydecke, ; Zhang, Lyu, Shang, Niu, & Liang, ). The cylindrical stud attachment (Locator) is widely used in general practice and has proven to be effective in IOD retention as well as OHRQoL improvement (Bilhan, Geckili, Sulun, & Bilgin, ; Enami et al, ; Fernandez‐Estevan, Selva‐Otaolaurruchi, Montero, & Sola‐Ruiz, ; Khalid, Yunus, Ibrahim, Elkezza, & Masood, ; Kleis, Kämmerer, Hartmann, Al‐Nawas, & Wagner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing technology and innovations, complete edentulism does not seem to be eradicated in the near future (4). Today, MODs seem to have taken over conventional complete dentures, since more and more studies reporting favorable outcomes of implant-retained overdentures are being published (29,32,33). According to the results of the present study, and the literature, patients with implant-supported MODs are satisfied with the outcome of MOD-treatment.…”
Section: Discussionsupporting
confidence: 59%
“…Dental loss is highly prevalent in the elderly population, causing esthetic, functional, psychological, and social inconvenience to the individual . Edentulism changes life perspective, feeding habits, interpersonal communication, self‐esteem, and quality of life in general …”
mentioning
confidence: 99%
“…3 Edentulism changes life perspective, feeding habits, interpersonal communication, self-esteem, and quality of life in general. 4,5 Conventional complete dentures are still widely used to rehabilitate edentulous individuals in regions with economic limitations. 6,7 However, a large number of complete denture wearers complain about the lack of retention and stability, especially in the mandible, which directly influences the masticatory function.…”
mentioning
confidence: 99%